RANDOMIZED DOUBLE BLIND PLACEBO CONTROLLED CLINICAL STUDY OF CYMBOPOGAN CITRATUS IN INFLUENZA (AYUSHDHARA, 2020)
Background: Influenza, or flu, is a respiratory illness that is caused by a virus. As Influenza is known to be highly contagious and there by affecting working community at large, a natural; cost effective remedy can help sail through the course of illness with much ease.The plant Cymbopogon citratus (DC) Stapf. commonly known as Lemon grass belongs to Poaceae family and is a native of tropical countries. Various studies have been done on the plant to reveal its potential therapeutic effects. Thus this study untended to evaluate its efficacy in the management of Influenza and its symptoms.Methodology: Randomized double blind placebo controlled clinical study. 62 patients of age group 20- 50 years, suffering from Influenza and fulfilling the diagnostic criteria were selected and randomly grouped into trial (Group I - 31 patients) and control group (Group II - 31 patients received the Placebo- Distilled water 25ml 3 times daily). Both the groups were given Paracetamol 500mg/kg body weight as rescue medicine if required.Observation & Results: The signs and symptoms of Influenza which were exhibited in patients when subjected to the Trial medication showed good results. The quality of life in them was better compared to control group.Conclusion: The current study helped to confirm the effect of the plant Cymbopogon citratus (DC) Stapf. in influenza. In Trial group, significantly better remission of associated signs and symptoms of influenza was found compared to control group. This would help us create an increased awareness amongst the public about the use of herbal medicines in either cure or as add on therapy in the management of Influenza.